Adopters and non-adopters of drones in humanitarian operations: An empirical evidence from a developing country - Bertha Maya Sopha; Anna Maria Sri Asih; Juhri Iwan Agriawan (Progress in Disaster Science, 2024)
Drones, or unmanned aerial vehicles (UAVs), are becoming more popular as a means of assisting with humanitarian operations. However, divisive concerns toward drone implementation exist. The present study aims to characterize drone adopters and non-adopters and explore significant determinants underlying drone acceptance for humanitarian operations in a developing country. A disaster-prone developing country of Indonesia was selected as a studied case. An empirical survey involving 439 rescuers from governmental disaster agencies, international and national non-governmental organizations was conducted in 2023. Independent t-test/chi-squared test and Ordinary Least Squares (OLS) regression were used for characterization and determinant identification, respectively. The drone adopters and non-adopters are significantly different with respect to age, gender, education, regions, work experiences, knowledge, personal innovativeness, and perceptions of drone durability, institutional support/policy, regulation, standard. Gender, education, knowledge, awareness, personal innovativeness, technology maturity, drone durability, reliability in extreme weather, GPS signal, optimal drone routing, noise and visual pollution, and misuse risk, are significant determinants contributing to potential adoption. The findings imply that initiatives encouraging drone should be customized for the intended individuals and that not only drone technology but also the facilitation of efficient operation should be enabled to drive the further uptake of drones. Future research extending the study in various disaster-prone areas and exploring the interrelationships among driving forces on drone acceptance, drone adoption decision making involving various stakeholders, and other customized strategies targeting specific rescuers are hence suggested.